Adaptation of Adolescent Behavioral Activation Program and Investigation of Its Effectiveness by Mixed Method - Seçer, İsmail; Koşan, Yavuz (My University, 2022)
In this study, the Adolescent Behavioral Activation Program (A-BAP) based on behavioral activation (BA) therapy to reduce depressive symptoms in adolescents was adapted to Turkish culture, and its effectiveness was tested with intervention design, one of the mixed method designs. In this direction, experimental and control groups were formed with 20 students studying in three different high schools in Turkey and with highly elevated depressive symptoms. The study group was determined by nested sampling from mixed-method sampling strategies. The starting point of this study is the absence of any BA-based practice to reduce adolescent depression in Turkey. In this direction, experimental and control groups were formed with 20 students studying in three different high schools in Turkey and with highly elevated depressive symptoms. The adapted A-BAP was applied individually to the students in the experimental group for 12 weeks. Three sessions were also held with the parents of the students in the experimental group. In the quantitative phase of the study, pre-test and post-test control groups paired patterns from semi-experimental designs, and a case study was used in the qualitative stage. The qualitative data of the study were collected from adolescents and their parents through semi-structured interviews and session evaluation forms. It was determined that the adapted BA-based A-BAP was an effective intervention in reducing depressive symptoms in the Turkish adolescent sample and provided a significant decrease in the depression scores of the participants in the experimental group . The qualitative findings show that adolescents perceive the A-BAP process as a factor contributing to making them feel better. Adolescents have reported that A-BAP is effective in reducing avoidance behavior, achieving anger control, and increasing self-esteem and social interaction. Parents consider A-BAP as a developer, educator, and practice that reduces depressive symptoms in their children. In addition, it was determined that the qualitative findings obtained supported the quantitative results. Since the study is the first application of BA therapy in Turkey, it is thought that it will contribute to new studies in Turkey and intercultural studies at the international level.